VEGETATION ANALYSIS ON RECLAMATION AREA OF COAL MINE OF PT. BUKIT ASAM TANJUNG ENIM, SOUTH SUMATERA - Prasetyo, Rendra Bayu; Marisa, Hanifa; Sarno, - (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
The Research of Vegetation Analysis on Reclamation Area of Coal Mine of PT. Bukit Asam Tanjung Enim, South Sumatera was aimed to determine the types of vegetation that composing reclamation area was found in PT. Bukit Asam in terms of structure and composition. The research has been done in November until Desember 2014, in four reclamation area at PT. Bukit Asam, namely the area of reclaimed the Muara Tiga Besar Selatan, Mahayung, Klawas Timur, and the Muara Tiga Selatan having different strata age. the vegetation data includes rate of growth seedlings, saplings, poles, and tree obtained through transek method in the form plot lane. In each transect made a plot in size 20x20 m for tree level, 10 x 10 for poles level, 5x5 for saplings level, and 2x2 m for seedling and cover plants level. The results of this research, in the Muara Tiga Besar Selatan area was obtained the vegetation seedlings-cover plants and saplings level, each of 17 and 7 species. In the area Mahayung are only found level vegetation of seedlings-cover plants as many of 13 species. For the area Klawas Timur and Muara Tiga Besar Selatan was obtained growth level of seedlings-cover plants, saplings, poles, and tree each of 20, 4. 3, dan 2 species for Klawas Timur area, while on Muara Tiga Selatan area each obtained 19, 8, 7, and 3 species.The diversity index of species, overall in all area of reclamation and rate of growth included in the low category with value 0 ≤ H’ ≤ 2.Key words : PT. Bukit Asam, Vegetation Analysis, Reclamation, Transect, Diversity Index